Mandatory COVID-19 Vaccination in the Health Sector: a Comparative Approach Between the Greek and American Examples. - Pervou, Ioanna; Mpogiatzidis, Panagiotis (Health Care Analysis, 2025)
A few months after national vaccination campaigns were initiated around early 2021, the discussion regarding the mandatory vaccination of healthcare workers started gaining ground in most European states and also in the United States. The debate on whether healthcare workers should be required to be vaccinated has been fueled by three main reasons: the high transmissibility rate of the Delta variant, which posed a significant risk to national healthcare systems across Europe and the Americas, as well placing high pressure on intensive care units even in the summer months (a); states' inability to impose general lockdowns and social distancing measures during the 2022 winter due to financial hardship and fears of an ongoing recession (b); and governmental unwillingness to implement restrictive measures, having in mind their populations' tiredness from previous lockdowns (c). This paper will explore the legal and managerial implications of mandatory vaccination among healthcare workers and will argue that it has the capacity to be a successful part of effective national healthcare systems in the search for responsible professionals to staff them. It will argue that national vaccination strategies are dependent on states' national healthcare models. It will show how the major difference in healthcare models of the two states chosen as examples have affected their vaccination policies and their reception by healthcare personnel. Finally, it will prove that the advantages of mandatory vaccination for healthcare personnel outweigh prospected disadvantages, irrespective of ethical, or legal justification is applied. This research will go through the key points of the legislative provisions of the two states (a); it will delve into their legal (b) and managerial implications (c); and finally, it will go through the policy questions which arose (d). It will prove how selective mandatory vaccination policies may be applied to national healthcare systems with foundational differences in their conception. Thus, it will demonstrate that selective mandatory vaccination is a viable option both for models approaching health from a societal perspective, and from the liberal ones.